A SYSTEMATIC APPROACH TO THE DEVELOPMENT OF LOGISTICS OF PRODUCTION ENTERPRISES - HONCHARUK, Andrii; KARPENKO, Vadym; SHLIAKHOVYI, Oleksandr; PIDKAMINSKYI, Mykola (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The study focuses on issues of organization and improvement of logistics activities of enterprises in the production sector of the national economy. The relevance of the tasks of forming an effective logistics system capable of ensuring the optimal and rational (in terms of time and financial and economic characteristics) movement of goods, material, information, personnel and other assets and values of business entities is revealed. On this basis, the purpose of the research is to justify the systematic approach to the development of logistics of production enterprises. New approaches and solutions in the field of organization and improvement of logistics systems of domestic enterprises in the production sectors of the national economy are defined and characterized. The prospects of further development and work on the construction of more rational and effective logistics systems of enterprises of the real sector of the national economy are indicated. It has been proven that the systematic approach allows to ensure a significantly higher efficiency of logistics management of enterprises of the production sector of the national economy, as it allows a comprehensive approach to the solution of the entire spectrum of tasks in this area. It is additionally argued that the system approach allows to combine and, therefore, to create a single system of elements of management of the processes of formation and development of logistics systems in business, in particular in the real sector of the national economy. It was concluded that the following tasks (elements of the management system) of the system for the development of logistics of the industrial enterprise should be identified and clearly outlined: understanding the significance of the logistics system; outlining the significance of managing the physical distribution of products/services and information; identification of general perspectives of the company's logistics system; standardization of the customer and business partner service system; selection of methods of transportation and storage of products / services, storage, analysis, processing of information; standardization of the inventory management and control system; processing of orders, adjustment of functioning of information systems; reviewing the logistics strategy. It was determined that the construction of a full-fledged logistics system of a production enterprise involves taking into account such components as, firstly, management activities; secondly, the logistics factors used; third, logistics results; fourth, activities that are closely related to logistics. At the center of such a system is the influence and interaction between suppliers and buyers, as well as the passage of the stages of the production and sales processes of products - from the supply of raw materials to full settlements with the end consumer.
Keywords: logistics; logistics systems; production; enterprises of the real sector of the economy; system approach; tools; means